Costs associated with treatment of insomnia in Alzheimer's disease caregivers: a comparison of mindfulness meditation and cognitive behavioral therapy for insomnia - Tanya G. K. Bentley; Daisy Castillo; Nina Sadeghi; Dominique Piber; Judith Carroll; Richard Olmstead; Michael R. Irwin (BMC, 2022)
Abstract Background Among the over 5 million informal caregivers for patients with Alzheimer's disease (AD) in the United States (US), over 60% experience insomnia. Research on insomnia treatment efficacy in AD caregivers is limited. An ongoing randomized non-inferiority clinical trial, the Caregiver Sleep Research study, is evaluating whether mindfulness meditation is non-inferior to cognitive behavioral therapy for insomnia (CBT-I) in the treatment of insomnia in AD caregivers. The present report examines estimated intervention costs in this ongoing trial. Methods Micro-costing was used to itemize and abstract costs of the two interventions: a mindfulness-based intervention known as mindful awareness practices for insomnia (MAP-I); and CBT-I. This approach involves collecting detailed data on resources utilized and the unit costs of those resources, thereby revealing actual resource use and economic costs for each treatment arm. Personnel time, patient time, and supplies were inventoried, and unit costs were applied. Caregiver time costs, including travel, were based on US Labor Bureau home-health aide national mean hourly wages; instructor/staff costs were based on hourly wages. Per-participant and program costs were calculated assuming individual- and group-delivery to reflect real-world implementation. Sensitivity analyses evaluated robustness of estimates. Results From the societal perspective, per-participant MAP-I costs were $1884 for individual and $1377 for group delivery; for CBT-I, these costs were $3978 and $1981, respectively. Compared with CBT-I, MAP-I provided cost savings of $2094 (53%) and $604 (30%) per treated caregiver for individual and group delivery, respectively. From the US healthcare system perspective, MAP-I vs. CBT-I participant savings were $1872 (65%) for individual and $382 (44%) for group interventions, respectively. For MAP-I and CBT-I, instructor in-class time was the highest cost component. Results were most sensitive to combined instructor time costs. Conclusions Treatment of insomnia with MAP-I, compared to CBT-I, yields substantial cost savings for society and the healthcare system. With this potential for cost savings, results of the ongoing non-inferiority trial have critical implications for insomnia treatment dissemination and its benefits to AD caregivers and other community populations with insomnia.